A new species of Foleyellides (Nematoda: Onchocercidae) parasite of Lithobates spp. (Amphibia: Ranidae) from Mexico with a key for the species of the genus - Romero-Mayén, Angeles R.; León-Règagnon, Virginia (Zootaxa, 2016)
Thirty-six Foleyellides mayenae n. sp. were recovered from the body cavity of Lithobates psilonota (Webb, 2001) and L. pustulosus (Boulenger, 1883) (Ranidae) from Jalisco and Nayarit, respectively. Foleyellides mayenae is the eleventh species described for the genus and the third for Mexican amphibians; it differs from the other species of the genus by the following combined characters: five pairs of caudal papillae, 1 pre-anal, 1 adanal and 3 post-cloacal, and the absence of a preanal plaque.